Vive la Révolution! : Long Term Returns of 1968 to the Angry Students - Eric Maurin; Sandra McNally (Institute for the Study of Labor (IZA), 2005)
The famous events of May 1968, starting with student riots, threw France into a state of turmoil. The period of ?revolution? coincided with the time in which important examinations are undertaken. Normal procedures were abandoned and the pass-rate for various qualifications increased enormously. These events were particularly important for students at an early (and highly selective) phase of higher education. They are shown to have pursued further years of education because thresholds were lowered at critical stages. These historic events provide a natural experiment to analyse the returns to years of higher education for the affected generation and to consider consequences for their children. Thus, we contribute to debate on two very controversial questions: What is the true causal relationship between educational attainment and its labour market value? Is there a causal relationship between the education of parents and that of their children? Unlike most of the literature, we consider the effect of an intervention which alters an individual?s years of higher education rather than compulsory schooling. The results show a relatively high return, which might indicate that private returns are higher for the former. Furthermore, the treatment group is on the margin of the higher education system. This study suggests that expanding the university system to accommodate such people can yield very high private returns. Hence our study suggests very positive effects of the ?1968 events? for affected cohorts and is of contemporary relevance given the current debate in many countries about widening access to higher education.
Keywords: I2; 330; higher education; intergenerational; wages; Bildungsertrag; Soziale Bewegung; Akademische Berufe; Frankreich